E-services evaluation criteria: the case of Azerbaijan - Yusifov, Farhad; Gurbanli, Aynur (Information & Media, 2018)
[full article in English]The development of evaluation and effective public administration mechanisms are crucial for providing effective e-government services. The article explores the international expertise in the field of the e-service evaluation process. The organization and provision of e-services in government entities, as well as the evaluation regarding the organization and functioning of information systems, are carried out by the “ASAN service” system in Azerbaijan. The evaluation of the organization and functioning of e-services is conducted by considering three determined criteria: the level of digitalization and relevance, the level of information openness and accessibility, and the level of convenience of use. The evaluation process of e-services allows for improving the level of services and the development of feedback mechanisms; currently, much attention is attributed to the development of citizen-centered services.
Keywords: e-service, e-government, e-service evaluation, public services, citizen-centered services